Antagonist Mold Exploration of Phytophthora spp. Pathogen on Apple Plant - Nugrahani, Meisarina; Suharjono, Suharjono; Endarto, Otto (Natural B, Journal of Health and Environmental Sciences, 2012)
The attack of Phytophthora spp. caused the descrease of apple crops production up to 90 %. Some antagonist mold species are able to inhibit the growth of Phytophthora pathogens onapple crops. The objectives of this research were to identifify and to study the potency of antagonist mold for inhibite the growth of Phytophthora spp. pathogens on apple crops. The Phytophthora spp. were isolated using baiting method with apple fruitÂ while antagonist molds were isolated by dilution method from soil sample of apple plantation. The inhibition assay of antagonist molds against Phytophthora was carried out by dual culture method. The isolated both of Phytophthora spp. and antagonist mold isolates were identified based on phenotype characters. The research result showed six molds namely Trichoderma sp.1, Trichoderma sp.4, Trichoderma sp.6, Aspergillus sp.2, Aspergillus sp.3 and Penicillium sp.1 which were antagonist on the Phytophthora pathogens onapple crops. Among the antagonist mold species, Trichoderma sp.6 had the highest inhibitory potency (62.95 %) while Penicillium sp.1 had the lowest inhibitory potency (28.82 %) against the growth of Phytophthora.Â